PENGEMBANGAN MEDIA KOMIK DIGITAL UNTUK MENINGKATKAN MINAT BELAJAR MATEMATIKA MATERI GEOMETRI BANGUN DATAR - Zifanny Ardini; Sukmawarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop learning media in the form of digital comics that can increase students' interest in learning Mathematics, especially in the material of flat geometry in elementary schools. The background of this study is based on the low interest of students in learning mathematics which is considered difficult and less interesting, as well as the limitations of learning media used by teachers in conveying abstract geometric concepts. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate) from Thiagarajan. The subjects of the trial in this study were fifth grade students at SD Swasta Kasih Ibu Medan. Data were obtained through validation questionnaires from material experts, media experts, teachers, and student learning interest questionnaires. The results of the study showed that the digital comic media developed had a high level of validity, good practicality, and significant effectiveness in increasing students' interest in learning. This media was declared suitable for use as a mathematics learning aid because it was able to visualize abstract concepts to be more concrete, fun, and easy for students to understand. Thus, digital comic media has proven to be an innovative solution in increasing students' interest in learning and enriching the variety of learning media in the classroom.